Clinico-pathological spectrum of small intestinal lesions at a tertiary care hospital - M.H. Prabhu Mural; N.V. Kalyan; Mallikarjun A. Pattanashetti; Shivakumar S. Inamdar (Al Ameen Medical College, 2020)
Background: Small intestine is affected by various diseases ranging from developmental abnormalities, inflammatory diseases, malignancies etc. This study was carried out to study the occurrence and evaluate histopathology of small intestinal lesions and ileocaecal region lesions. Methods: A cross sectional histopathological study of small intestinal and ileocaecal region lesions of 44 cases was carried out on surgical specimens and biopsy received from Department of Surgery from January 2016 to July 2017. Specimens were preserved and fixation was done in 10% buffered formalin. Subsequently processing was done and slides stained with Haematoxylin and Eosin. Histopathological diagnosis was noted for each case. The data was analysed using SPSS version 20. Categorical data was expressed in terms of rates, ratios and percentage. Results: A total of 44 cases were included, among which 25 were males and 19 were females, with peak occurrence in 60 - 70 years age group. Pain abdomen was the commonest symptom. Histopathology spectrum studied in small intestine lesions showed 28 cases (87.5%) were non-neoplastic, whereas 4 cases (12.5%) were neoplastic lesions. The most common non-neoplastic lesion seen was Tuberculosis intestine. Other lesions seen were Perforation, Ischemic enteritis with gangrene, etc. Neoplastic lesions included rare cases like GIST and Metastatic squamous cell carcinoma. In the ileocaecal region, tuberculosis intestine was the most common lesion. Other lesions were Crohns disease, diverticulosis, intusseption etc. Conclusion: There is wide spectrum of lesions seen in Small intestine and ileocaecal region. This study emphasises the need for early diagnosis of the disease through histopathology, which when correlated clinically will help the clinician to implement the appropriate treatment and improve the survival of the patients